Screening for Depression and Psychological Distress in a Currently Serving Military Population: The Diagnostic Accuracy of the K10 and the PHQ9. (December 2019) - Searle, Amelia K.; Van Hooff, Miranda; McFarlane, Alexander C.; Davies, Christopher E.; Tran, Thao; Hodson, Stephanie E.; Benassi, Helen P.; Steele, Nicole M.
This study is the first to examine the diagnostic accuracy of two depression screening scales—the Kessler Psychological Distress Scale (K10) and the Patient Health Questionnaire (PHQ)—in an entire regular-serving military population. Currently serving Australian Defence Force personnel ( n = 24, 481) completed the K10 and PHQ9. Then a targeted subsample (i.e., the analysis sample, n = 1, 730) completed a diagnostic interview to identify DSM-IV 30-day disorder. Weighted results represented the entire population ( N = 50, 049). Both scales similarly showed a good ability to discriminate between personnel with and without depressive disorders. Optimal cutoffs (19 for K10, 6 for PHQ9) showed high sensitivity and good specificity, and were similar to though slightly lower than those recommended in civilian populations. Both scales appear to be valid screens for depressive disorder in the military, using the cutoffs identified. As both performed similarly, scale choice may depend on other factors (e.g., availability of norms).